Tradisi "Toyang Roeng" pada Pernikahan Masyarakat Tande di Kecamatan Tammaro'do Sendana Kabupaten Majene - Nurul Amaliah; Andi Ima Kesuma (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2023)
The type of research used is a type of qualitative research with an anthropological approach. The data validity test was carried out using the triangulation technique stage. Data analysis techniques using data collection, data reduction, data display, verification and drawing conclusions. The informants in this study were village heads/district heads, community leaders, religious leaders, cultural figures, youth leaders, and the Tande community who carry out the toyang roeng tradition. The primary data was obtained directly through observation and interviews with several informants. While secondary data is obtained through photos, videos, books, journals, and other related data. The aim of this study was to find out the process of carrying out the toyang roeng tradition at the wedding of the Tande community in Kec. Tammero'do Sendana, Kab. Majene. The results showed that the process of carrying out the Toyang Roeng tradition at the wedding of the Tande community in Kec. Tammero'do Sendana, Kab. Majene is divided into three stages, namely the preparation stage for the toyang roeng tradition, the implementation stage for the toyang roeng tradition and the final stage of implementation. The meaning and symbol as a symbol of life in the toyang roeng tradition has an important meaning for people's lives and holds positive things in every ritual that is carried out. This study uses the theory of symbolic interactionism according to Herbert Blumer.